A case of 17 alpha-hydroxylase deficiency - Kim, Sung Mee (Clin Exp Reprod Med, 2015)
17α-hydroxylase and 17,20-lyase are enzymes encoded by the CYP17A1 gene and are required for the synthesis of sex steroids and cortisol. In 17α-hydroxylase deficiency, there are low blood levels of estrogens, androgens, and cortisol, and resultant compensatory increases in adrenocorticotrophic hormone that stimulate the production of 11-deoxycorticosterone and corticosterone. In turn, the excessive levels of mineralocorticoids lead to volume expansion and hypertension. Females with 17α-hydroxylase deficiency are characterized by primary amenorrhea and delayed puberty, with accompanying hypertension. Affected males usually have female external genitalia, a blind vagina, and intra-abdominal testes. The treatment of this disorder is centered on glucocorticoid and sex steroid replacement. In patients with 17α-hydroxylase deficiency who are being raised as females, estrogen should be supplemented, while genetically female patients with a uterus should also receive progesterone supplementation. Here, we report a case of a 21-year-old female with 17α-hydroxylase deficiency who had received inadequate treatment for a prolonged period of time. We also include a brief review of the recent literature on this disorder.